2019
DOI: 10.4149/bll_2019_071
|View full text |Cite
|
Sign up to set email alerts
|

The role of sex hormones and social determinants in assessment of facial attractiveness

Abstract: OBJECTIVES: The current study is focused on assessing the factors of attractiveness of opposite-sex individuals based on evaluating photographs of their faces. BACKGROUND: When assessing the attractiveness, factors of both, the assessed individual and the assessor play a role. The relationship of the preference for partners based on their physical appearance with the markers of prenatal testosterone is not fully understood. METHODS: Sex hormone levels were measured in saliva, while age, social status, income a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Wrinkles are a sign of older age, which is considered less attractive than a young appearance. 47 This also accounts for people who care more about the opinion of others and are more likely to have wrinkle treatment; wrinkles are often considered an esthetic flaw, which leads to higher insecurity. It has been shown that age prevention and psychosocial wellbeing are key motivators for cosmetic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wrinkles are a sign of older age, which is considered less attractive than a young appearance. 47 This also accounts for people who care more about the opinion of others and are more likely to have wrinkle treatment; wrinkles are often considered an esthetic flaw, which leads to higher insecurity. It has been shown that age prevention and psychosocial wellbeing are key motivators for cosmetic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…More wrinkles would be a factor to lower one's satisfaction. Wrinkles are a sign of older age, which is considered less attractive than a young appearance 47 . This also accounts for people who care more about the opinion of others and are more likely to have wrinkle treatment; wrinkles are often considered an esthetic flaw, which leads to higher insecurity.…”
Section: Discussionmentioning
confidence: 99%